Carbon monoxide detection with CMOS integrated thin film SnO2 gas sensor. (2017) - Lackner, Eva; Krainer, Johanna; Wimmer-Teubenbacher, Robert; Sosada, Florentyna; Deluca, Marco; Gspan, Christian; Rohracher, Karl; Wachmann, Ewald; Köck, Anton
Abstract: We present the integration of thin film SnO2 gas sensor on CMOS microchips. A spray pyrolysis process was used to deposit the gas sensitive film, with a thickness of 50 nm, on CMOS microhotplates. The exposure of the CMOS integrated gas sensor to carbon monoxide at different operating temperatures and humidity levels lead to a significant decrease in the sensor resistance. At an operating temperature of 375 °C a sensor response of almost 50% was achieved. The integration of the sensing material on CMOS microhotplates makes it possible to reduce the size and power consumption of metal oxide gas sensors.